Model Kesetimbangan Pada Adsorpsi Ion Logam Timbal (Pb2+) Menggunakan Hidroksiapatit - Dhamala Shobita Chandra; Ahmad Fadli; Komalasari Komalasari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
The needs for industrial wastewater treatment for heavy metal have been a concern. Adsorption using hydroxyapatite (HAp) as adsorbent is one of the choice to remove heavy metal content economically and efficiently. The objective of this research is to study the effect of temperature and weight of adsorbent in adsorption as well as determine adsorption equilibrium model in the lead ion adsorption using Langmuir, Freundlich, and Temkin model. Lead (Pb2+) solution of 5 ppm was added with 0.9 gram, 1.0 gram, and 1.2 gram of HAp in a beaker glass and stirred with stirring rate of 300 rpm and temperature variation of 30°C, 40°C, dan 50°C. Solution samples was taken every 10 minutes until equilibrium and and analyzed for the remaining Pb2+ using ICP-OES instrument. The results showed that the increase of temperature reduce the rate of Pb2+ adsorption and increased of the weight of adsorbent increase the percentage of adsorption. The equilibrium time of lead ion adsorption is 50 minutes, with optimum condition obtained on 30°C and hydroxyapatite adition 1.2 gram. Equilibrium model describes the heat of adsorption and thermodynamics parameter of adsorption process, ∆H = -0.53 kJ/mole, ∆G < 0, ∆S = -144.1406 kJ/mole). Keywords: hydroxyapatite, adsorption, adsorpsion equilibrium model, lead (Pb2+)